The Extraordinary Leader : Turning Good Managers into Great Leaders, 2nd Edition - Zenger, John; Folkman, Joseph (McGraw-Hill, 2009)
People can learn how to lead. This was the position John H. Zenger and Joseph R. Folkman took when they wrote their now-classic leadership book The Extraordinary Leader -and it's a fact they reinforce in this new, completely updated edition of their bestseller. When it was first published, The Extraordinary Leader immediately attracted a wide audience of aspiring leaders drawn to its unique feature: the extensive use of scientific studies and hard data, which served to demystify the concept of leadership and get readers thinking about the subject in a pragmatic way. Now, Zenger and Folkman revisit the subject to address leaders' most pressing concerns today. The result is an up-to-date, essential leadership guide for the twenty-first century that includes: Late-breaking research on the psychology of leadership New information on leading in a global environment A breakthrough case study on measuring improved leadership behavior Studies revealing the importance of follow-through The Extraordinary Leader is a remarkable combination of expert insight and extensive research. The authors analyzed more than 200,000 assessments describing 20,000 managers-by far the most expansive research ever conducted for a leadership book. Zenger and Folkman have created the leadership book of the ages. The Extraordinary Leader explains how to build leadership skills that will take you and your organization to unimagined success.